Prevalence and Risk Factors of Asymptomatic Left Ventricular Hypertrophy among Type 2 Diabetic Patients in Urban and Rural Settings - Muhammad Zahid Ali Raza, Aamir Siddique, Shaoib Ahmed Zia, Tayyab Mohyuddin, Arslan Aslam Chahudhary, Faiza Altaf, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Left ventricular hypertrophy (LVH) is a prevalent yet often asymptomatic cardiovascular complication in patients with type 2 diabetes mellitus (T2DM), contributing significantly to increased morbidity and mortality. Early detection of asymptomatic LVH is crucial, particularly in regions with disparities in healthcare access between urban and rural populations. Objective: This study aimed to determine the prevalence and associated risk factors of asymptomatic LVH among T2DM patients in both urban and rural settings. Methodology: A cross-sectional study was conducted at the Department of Cardiology, Nawaz Shareef Medical College / Aziz Bhatti Shaheed Teaching Hospital, Gujrat, Pakistan. A total of 100 patients with T2DM were enrolled, with 50 each from urban and rural populations. Clinical assessments included demographic data, anthropometric measurements, and medical history. Biochemical investigations comprised fasting blood glucose (FBG), HbA1c, lipid profile, high-sensitivity C-reactive protein (hs-CRP), and serum insulin levels. Insulin resistance was calculated using the Homeostatic Model Assessment for Insulin Resistance (HOMA-IR). Transthoracic echocardiography was performed to calculate left ventricular mass index (LVMI), with LVH defined based on standard gender-specific criteria. Results: The prevalence of asymptomatic LVH was 60% in the urban group and 48% in the rural group (p=0.23). Urban patients had significantly higher BMI (28.6 vs. 26.9 kg/m², p=0.01), LDL (128 vs. 121 mg/dL, p=0.04), hs-CRP (5.2 vs. 4.6 mg/L, p=0.03), and LVMI (118.4 vs. 113.2 g/m², p=0.01), while HDL was significantly lower (38 vs. 41 mg/dL, p=0.02). HOMA-IR values were elevated in both groups, showing borderline significance. Conclusion: Asymptomatic LVH is common in both urban and rural T2DM patients, with urban individuals exhibiting a more adverse cardiometabolic profile characterized by obesity, dyslipidemia, and subclinical inflammation. These findings highlight the importance of routine cardiac screening and targeted metabolic risk reduction strategies to prevent progression to overt cardiac disease. Keywords: Diabetes, Hypertrophy, Echocardiography, Insulin, Cholesterol, Inflammation, Screening